Two Volatile Organic Compounds Trigger Plant Self-Defense against a Bacterial Pathogen and a Sucking Insect in Cucumber under Open Field Conditions - Song, Geun Cheol (Molecular Diversity Preservation International (MDPI), 2013)
Systemic acquired resistance (SAR) is a plant self-defense mechanism against a broad-range of pathogens and insect pests. Among chemical SAR triggers, plant and bacterial volatiles are promising candidates for use in pest management, as these volatiles are highly effective, inexpensive, and can be employed at relatively low concentrations compared with agrochemicals. However, such volatiles have some drawbacks, including the high evaporation rate of these compounds after application in the open field, their negative effects on plant growth, and their inconsistent levels of effectiveness. Here, we demonstrate the effectiveness of volatile organic compound (VOC)-mediated induced resistance against both the bacterial angular leaf spot pathogen, Pseudononas syringae pv. lachrymans, and the sucking insect aphid, Myzus persicae, in the open field. Using the VOCs 3-pentanol and 2-butanone where fruit yields increased gave unexpectedly, a significant increase in the number of ladybird beetles, Coccinella septempunctata, a natural enemy of aphids. The defense-related gene CsLOX was induced by VOC treatment, indicating that triggering the oxylipin pathway in response to the emission of green leaf volatiles can recruit the natural enemy of aphids. These results demonstrate that VOCs may help prevent plant disease and insect damage by eliciting induced resistance, even in open fields.